2005
DOI: 10.1038/ni1206
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian defensins in the antimicrobial immune response

Abstract: Defensins are peptidic components of the innate immune system of plants and animals. In mammals, defensins have evolved to have a central function in the host defense properties of granulocytic leukocytes, mucosal surfaces, skin and other epithelia. This review focuses on the biological functions of three structural subgroups of mammalian defensins and the evidence for their involvement as effectors of antimicrobial innate immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
955
1
16

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,055 publications
(984 citation statements)
references
References 102 publications
5
955
1
16
Order By: Relevance
“…Defensins are well-known cysteine-rich peptides and are classified into three types: α-(human neutrophil peptide, HNP), β-(hBD), and θ -defensins [39][40][41][42][43]. α-and β-defensins are found in humans, while θ -defensin is not, although a human orthologue of this defensin has been described [44].…”
Section: Defensinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Defensins are well-known cysteine-rich peptides and are classified into three types: α-(human neutrophil peptide, HNP), β-(hBD), and θ -defensins [39][40][41][42][43]. α-and β-defensins are found in humans, while θ -defensin is not, although a human orthologue of this defensin has been described [44].…”
Section: Defensinsmentioning
confidence: 99%
“…α-and β-defensins differ in their location, the length of amino acid residues, and the pairing of disulphide bonds. Recently, these peptides were found to have not only anti-microbial activity, but also chemokine-like activity [43,45]. The characteristics of both defensins are summarized below.…”
Section: Defensinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Defensins and cathelicidins are the two major classes of mammalian antimicrobial peptides [2]. Previous studies have shown that defensins are microbicidal against Gram-positive and Gram-negative bacteria, yeast, fungi, spirochetes, protozoa, and enveloped viruses [3,4]. Moreover, some defensins are known to act as chemokines that activate the adaptive immune response [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some defensins are known to act as chemokines that activate the adaptive immune response [2][3][4][5]. The mammalian defensins are characterized by six cysteine residues forming three intramolecular disulfide bridges, and are divided into two subfamilies, α-and β-defensins, based on the amino acid sequence similarities and the linkages of the disulfide bonds [3][4][5].…”
Section: Introductionmentioning
confidence: 99%